Tetany Due to Refeeding Syndrome in A Recently Diagnosed Child with Celiac Disease - Mantadakis, Elpis; Alexiadou, Sonia; Totikidis, George; Sotiriadou, Foteini; Kolona, Christina; Markidou, Sophia; Filippidis, Stelios; Fotoulaki, Maria (Archives of Clinical and Medical Case Reports, 2019)
Celiac disease (CD) occurs in genetically predisposed individuals, and usually presents with gastrointestinal symptoms. Hypocalcemia with associated tetany has rarely been reported as the presenting symptom of CD. A 4-year-old girl presented to us with bilateral painful carpopedal spasm. The patient was diagnosed with CD one month ago, and although adherent with her gluten-free diet, she consumed large amounts of gluten-free foods due to exceptional voracious appetite. Low serum calcium, phosphorus and vitamin D were found on admission and were corrected with appropriate parenteral and oral administration. Symptomatic hypocalcemia can occur in the context of celiac crisis and/or refeeding syndrome, a disorder characterized by the sudden shift in fluids and electrolytes that occurs in malnourished patients, who are refed without restrictions. Newly diagnosed malnourished patients with CD should be advised to increase their oral intake gradually, and to closely monitor their serum electrolytes.